The Relation of Human and Village Development in Indonesia - Royhan Faradis; Uswatun Nurul Afifah (Universitas Bangka Belitung, 2021)
Indonesia experienced a recession in the third quarter of 2020 due to the Covid-19 pandemic. This economic crisis is expected to last for quite a long time. Previous studies have shown that the prolonged economic crisis has a significant effect on the decline in human quality. The government must be able to control this by continuing to stabilize human development even though the pandemic is ongoing. One way is to continue providing basic services for the community. Basic services can easily be managed by the central government through the village government which is regulated by law. This research shows that there is a significant positive relationship between human development and rural areas. Another fact obtained is that there are 14 provinces categorized as regions with vicious development where their human and rural development are below the national figure. Papua and West Papua are provinces with the deepest development gap compared to other provinces.